Frontispiece: Long‐Range Cationic Disordering Induces two Distinct Degradation Pathways in Co‐Free Ni‐Rich Layered Cathodes. Issue 12 (6th March 2023) - Hua, Weibo; Zhang, Jilu; Wang, Suning; Cheng, Yi; Li, Hang; Tseng, Jochi; Wu, Zhonghua; Shen, Chong‐Heng; Dolotko, Oleksandr; Liu, Hao; Hung, Sung‐Fu; Tang, Wei; et al.
Abstract : Batteries . In their Research Article (e202214880 ), Weibo Hua, Wei Tang, Sylvio Indris, Xiaodong Guo et al. synthesized a series of Ni‐rich Li(NiAl)O2 oxides through tailoring the heating temperature. The oxides with high cation disorder experience a comparably homogeneous fatigue process upon extended cycling.